Acta Medica Indonesiana - The Indonesian Journal of Internal Medicine 333 Supraclavicular Lymphnodes: Unusual Manifestation of Metastase Adenocarcinoma Colon - Harijono Achmad; Rofika Hanifa (Acta Medica Indonesiana)
We report a patient with supraclavicular lymph node metastasis from an undetectable adenocarcinoma of the transverse colon, who presented with cough and was diagnosed with typhoid fever, bronchitis as well as liver metastasis. There were an abdominal fullness, weight loss, constipation, pencil-like stool with mucous and blood, low-grade fever, bone ache, and tea-color urine. The first colonoscopy revealed lymphocytic ileitis and microscopic findings also showed lymphocytic ileitis. Abdominal USG and CT revealed liver metastasis of unknown origin. Based on the clinical sign and symptoms, we suspected that colorectal carcinoma was the primary site. Then, the second colonoscopy was performed and it revealed a small polyp, which was followed with a biopsy and the result supported a well-differentiated colon adenocarcinoma. Similar result was also revealed by the histopathological evaluation. This is an unusual case of liver and supraclavicular lymph node metastasis arising from a small polyp adenocacinoma of the transverse colon.